2017
DOI: 10.1016/j.ram.2016.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Blastocystis spp.: avances, controversias y desafíos futuros

Abstract: Blastocystis spp. is the most common protozoan detected in human stool samples. In developing countries, infection rates are higher than 20%. The presence of this parasite in the feces of several host species suggests its zoonotic potential. The clinical relevance and the pathogenic role of Blastocystis spp. in the intestinal tract remain unclear. There are several clinical reports that recognize it as the etiologic agent of several intestinal disorders such as diarrhea, inflammatory bowel disease and ulcerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0
16

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 82 publications
3
13
0
16
Order By: Relevance
“…These findings are in agreement with results obtained using microscopy in Colombia that showed significant frequency in Caribbean regions such as Santa Marta (62.6%) and in Andean areas such as Santander (25%), Bogotá (22.4%), Quindío (36.4%) and Cundinamarca (34.8%) (Londono-Franco et al, 2014). When performing subtyping of Blastocystis, we identified STs 1-4, 8 and 9, with STs 1-3 having the highest frequency as reported by Del Coco and collaborators in a review made in 2017 and another study in Brazil (Del Coco et al, 2017;Malheiros et al, 2011). The municipality of Poré, Casanare showed the greatest diversity of STs.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…These findings are in agreement with results obtained using microscopy in Colombia that showed significant frequency in Caribbean regions such as Santa Marta (62.6%) and in Andean areas such as Santander (25%), Bogotá (22.4%), Quindío (36.4%) and Cundinamarca (34.8%) (Londono-Franco et al, 2014). When performing subtyping of Blastocystis, we identified STs 1-4, 8 and 9, with STs 1-3 having the highest frequency as reported by Del Coco and collaborators in a review made in 2017 and another study in Brazil (Del Coco et al, 2017;Malheiros et al, 2011). The municipality of Poré, Casanare showed the greatest diversity of STs.…”
Section: Discussionmentioning
confidence: 73%
“…On the other hand, members of the genus Blastocystis can be classified into 17 subtypes (STs) (Stensvold et al, 2007) based on polymorphisms of 18S rDNA (Scicluna, Tawari & Clark, 2006). In humans, STs 1-3 are common in both Europe and South America (Del Coco et al, 2017;Malheiros et al, 2011;Ramírez et al, 2016;Santin et al, 2011), while ST4 is commonly found in Europe (Stensvold et al, 2011;Wawrzyniak et al, 2013) and was possibly associated with an enzootic cycle in nonhuman primates in Latin America (Ramírez et al, 2014;Santin et al, 2011). Approximately 20 different species have been identified within the genus Cryptosporidium, where Cryptosporidium hominis and Cryptosporidium parvum are the most common pathogens infecting humans (Feng & Xiao, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Este parásito se ha asociado con desórdenes intestinales (diarrea, inflamación intestinal, síndrome del intestino irritable, colitis ulcerosa) y extraintestinales (urticaria y anemia ferropénica). Sin embargo, su papel como patógeno es aún controversial porque se desconoce si sólo se comporta como patógeno bajo determinadas circunstancias, por ejemplo, cuando coexiste con otros parásitos o si la carga parasitaria es elevada (del Coco et al, 2017).…”
Section: Discussionunclassified
“…amebas, flagelados, coccidios) están ampliamente distribuidas en el mundo y se estima que alrededor de 200 millones de personas están infectadas por Giardia lamblia y un billón por Blastocystis sp. (Osman et al, 2016;del Coco et al, 2017).…”
Section: Parásitos Intestinales Y Su Importancia En Saludunclassified
See 1 more Smart Citation